2019
DOI: 10.3390/nu11102289
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Caffeine Expectancies on Simulated Soccer Performance in Recreational Individuals

Abstract: Caffeine (CAF) has been reported to improve various facets associated with successful soccer play, including gross motor skill performance, endurance capacity and cognition. These benefits are primarily attributed to pharmacological mechanisms. However, evidence assessing CAF’s overall effects on soccer performance are sparse with no studies accounting for CAF’s potential psychological impact. Therefore, the aim of this study was to assess CAF’s psychological vs. pharmacological influence on various facets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…The lack of placebo effect of caffeine in individuals habituated to caffeine may be reinforced by outcomes of previous investigations. While the placebo effect of caffeine has been con rmed by using several depictive protocols [9,10,[12][13][14][15][16][17][18], the two investigations carried out with participants habituated to caffeine showed that the deception was not successful. Foad et al [14] found that, in participants ingesting at least 300 mg/day of caffeine, informing that they had received caffeine, when they had ingested placebo, was not effective at increasing performance during a 40-km cycling time trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of placebo effect of caffeine in individuals habituated to caffeine may be reinforced by outcomes of previous investigations. While the placebo effect of caffeine has been con rmed by using several depictive protocols [9,10,[12][13][14][15][16][17][18], the two investigations carried out with participants habituated to caffeine showed that the deception was not successful. Foad et al [14] found that, in participants ingesting at least 300 mg/day of caffeine, informing that they had received caffeine, when they had ingested placebo, was not effective at increasing performance during a 40-km cycling time trial.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study did not contain a double-dissociation design. This is because we did not aim to study the additive effect of being informed of receiving caffeine plus actually receiving caffeine, as previous investigations have done [17]. Instead, the purpose of the current investigation was to determine in isolation the placebo effect of caffeine in women athletes habituated to this substance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the concentration of caffeine in post-competition urine samples, it has been found that about three out of four athletes consume caffeine or caffeine-containing products to increase performance [14]. Interestingly, the investigation by Shabir et al [15], who used a double-dissociation experimental design where caffeine and a placebo were administered in situations in which participants were informed or misinformed of the substance that they had ingested, determined that part of the ergogenic effect of caffeine on human performance is explained by the psychological impact of the expectancy of ergogenicity that caffeine produces in athletes. Thus, believing to have ingested caffeine, or feeling the stimulation that it produces, might be an important part of the actual ergogenic effect of caffeine [16].…”
mentioning
confidence: 99%
“…Thus, believing to have ingested caffeine, or feeling the stimulation that it produces, might be an important part of the actual ergogenic effect of caffeine [16]. In this regard, caffeine ergogenicity can be obtained by the synergistic action of the pharmacological effect of this substance on the central nervous system [8] and in other peripheral tissues [17], together with the psychological effect of this potent stimulant [15].…”
mentioning
confidence: 99%